Day-Ahead Operation of an Urban Energy System Considering Traffic Flows and Peak Shaving - Peng, Yan; Ma, Junchao; Lu, Chengyu; Chen, Sheng; Pei, Lei (Frontiers in Energy Research, 2022)
With the increasing penetration of new-type loads such as electric vehicles and hydrogen fuel vehicles in urban power grid, the peak-to-valley load difference increases sharply, and a multi-energy coordination model is desirable. This paper proposes a day-ahead operation model of an urban energy system considering traffic flows and peak shaving, which can positively contribute to multi-energy complement and low-carbon emission. The proposed model minimizes the total of electricity cost and gas cost by optimizing charging and discharging strategy of energy storage, in which the output of wind turbine and energy management of energy hub (EH) is adaptively adjusted. The urban energy system is represented by a second-order cone (SOC) energy flow model, and hence the optimization problem is modeled as a mixed integer SOC programming (MISOCP). Finally, test results on an integrated urban energy network indicates that the energy storage and multi-energy coordination can alleviate the peak load cutting and valley filling. The relationship between urban grid operation cost and peak-valley difference is also discussed. The maximum utilization of RESs using GVs has been presented in this paper to illustrate cost and emission reductions for a sustainable integrated electricity and transportation infrastructure.